Premenstrual Syndrome (PMS) and the Related Symptoms Among Students of Iran University of Medical Sciences (IUMS) - F. Shahpoorian; Z. Mahmoodi; F. Hosseini; F. Bastani; S. Parsay (Iran University of Medical Sciences, 2006)
Premenstrual syndrome is one of the most common disorder in women with reproductive age. The aim of this paper was to investigate the frequency and the intensity of this syndrome and the related signs and symptoms.   Five hundred students who were enrolled at BS level in the academic year 1384 at the schools of nursing-midwifery as well as the school Management of IUMS, were included in the study. They were asked to complete the premenstrual daily symptom diary (PDSD) for 2 months. The students with PMS, were confirmed according to the APA criteria and their intensity were assessed by the mean of scorces of each sign which varied from 0 to 3.   In this study, the response rate was about 50% (255). Out of the 255 students, 200 students (78.43%) were sufferring PMS to some degrees (62% mild, 36% moderate, 2% severe). Mood symptoms in 24% and the behavioral symptoms in 3% of the subjects were in severe level. None of the students suffered from sever physical symptoms.   The study results revealed a significant positive relationship between behavioral symptoms and physical mood symptoms (r=0.55, r=0.398, P=0.00) respectively. Also there was a significant relatinship between physical symptoms and mood symptoms (r=0.305, P=0.00).   In this study the investigators concluded that PMS can be considered as a common disorder in young iranian women at the reproductive age. To detect and diagnose the PMS related symptoms, could help provide the most effective treatment strategies. Future studies is recommended to find out the risk factors of the PMS and appropriate therapies.